Qualitative Evaluation of a Toddlers’ Speech Delay Early Detection Poster - Sheba, Shiane Hanako; Arum, Euis Reliyanti; Ekasari, Tetty (Research Collaboration Community (Rescollacom), 2023)
The estimated number of 0 to 4-years-old children with speech disorders in Indonesia is 1.3 million people. If they are not treated properly, they will have serious consequences in adulthood. The Ministry of health of Indonesia has launched a speech disorder detection in The Child Development Monitoring Programs carried out by Posyandu cadres or Community Health Center officers. To support the program, a poster design for the early Detection of Speech Disorders in Toddlers (DeGabbi) has been created. Prior to dissemination, it is necessary to evaluate the effectiveness of the poster by conducting qualitative research. FGDs with toddlers’ mothers and posyandu cadres were conducted using an open interview guideline regarding the message, the language, and the appearance of the poster. Triangulation was carried out on Puskesmas officers, media design experts, and Indonesian language experts. Prior to the FGD, informants were asked to look at Degabbi's poster on the room wall for 5 minutes. Results of the FGD showed that all informants understood the poster messages that stated,